Retrospective Analysis of Mini-Open Repair Versus Open Repair for Acute Achilles Tendon Ruptures. Issue 1 (February 2013) - Klein, Erin E.; Weil, Lowell; Baker, Jeffrey R.; Weil, Lowell Scott; Sung, Wenjay; Knight, Jessica
Purpose : Debate exists over optimal treatment for acute Achilles tendon ruptures. Recent literature suggests the mini-open technique may provide the reliability of the open repair with the decreased complication rate of non-operative treatment. This retrospective review compares acute tendon ruptures treated with one of two techniques: open repair (TO) or mini-open repair (MOA). Methods & Results : Records were reviewed and 34 patients were found to meet the inclusion criteria for open or mini-open repair of an acute Achilles tendon rupture with follow up of at least 12 months. TO (n=16) and MOA (n=18) had no statistically significant differences in age at time of injury [TO: 41 + 2.5 years (range 20 – 68); MOA: 46 + 2.5 years (range 33 – 73)] or time between injury and surgical repair [TO: 15 + 2 days (range 2 – 30); MOA: 15 + 2 days (range 2 – 30)]. Post-operative VISA-A scores were 82 + 10 (range 42 – 98) and 92 + 5 (range 66 – 100) for TO and MOA, respectively. Significant differences were found in the time between surgical intervention and beginning of rehabilitation [TO: Post op day 37 + 5 (range 21 – 46); MOA: Post op day 19 + 2 (range 7 – 32)] and the time between surgical intervention and full return to activity [TO: Post op month 7 + 1 (range 4 – 11); MOA: Post op month 5 + 0.6 (range 4 – 11)]. Conclusion : These results suggest that the mini-open repair provides acceptable surgical outcomes while optimizing patient function after Achilles tendon repair. Level of Evidence: Therapeutic, Level III: Retrospective Comparative